2019
DOI: 10.22440/elit.1.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exchange Rate Fluctuation on the Performance of Manufacturing Firms: An Empirical Evidence from Ghana

Abstract: This study examines the effect of exchange rate fluctuations on the performance of manufacturing firms in Ghana for the period 1990 to 2018. The study uses the bounds test approach to cointegration within the framework of autoregressive distributed lags model as the estimation strategy. The results reveal that exchange rate and monetary policy rate has a negative and significant relationship with manufacturing firm performance. It was also found that inflation, trade openness, and investment have significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The study followed previous studies (Adabor & Buabeng, 2020;Adabor et al, 2020;Buabeng et al, 2019aBuabeng et al, , 2019bCantah & Asmah, 2015) and specify the effect of natural resource (oil and gas resource rent specifically) on economic growth in a functional form as follows:…”
Section: Model Specificationmentioning
confidence: 99%
“…The study followed previous studies (Adabor & Buabeng, 2020;Adabor et al, 2020;Buabeng et al, 2019aBuabeng et al, , 2019bCantah & Asmah, 2015) and specify the effect of natural resource (oil and gas resource rent specifically) on economic growth in a functional form as follows:…”
Section: Model Specificationmentioning
confidence: 99%
“…The study examined the causal link between economic growth and oil revenue by following previous empirical studies (Adabor and Buabeng, 2020; Buabeng et al , 2019; Adabor et al , 2020) to specify a general model as shown below: …”
Section: Introductionmentioning
confidence: 99%
“…The study applies the autoregressive distributed lag (ARDL) as the estimation technique and the study found that the performance of manufacturing firms is positively related with exchange rate significantly. In a related study Boateng (2019) investigated the effect of exchange rate on the financial performance of manufacturing firms in Ghana using return on asset and equity as the dependent variable for the period 2009 to 2017. The study used imports, foreign direct investment and nominal interest rate as control variables and applies the panel regression as the estimation.…”
Section: Empirical Literaturementioning
confidence: 99%